Association between daily eating frequency and mortality in people with diabetes: Findings from NHANES 1999–2014 - Xie, Jing; Wang, Zhenwei; Zhang, Xin; Wang, Junjie; Feng, Wei; Hu, Yifang; Liu, Naifeng; Liu, Yun (Frontiers in Nutrition, 2023)
Background: Previous studies have shown that increasing frequency of eating is beneficial in terms of cardiovascular metabolic risk factors, however, limited evidence is available for the association between daily eating frequency and mortality, especially in people with diabetes. Therefore, we aimed to explore the association between eating frequency and long-term mortality in populations with diabetes. Methods: We selected 4,924 individuals suffering from diabetes (mean age: 57.77 years; 51.3% male) from the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2014. Daily eating frequency was used as the exposure factor in this study. We extracted the mortality data from the National Death Index records and matched them with the population of NHANES. All participants were followed up from being enrolled in NHANES to December 31, 2015. Using multivariate Cox proportional hazards regression, Kaplan-Meier survival curves and restricted cubic spline to assess the associations between eating frequency and all-cause and cause-specific mortality among people with diabetes. Results: During 34,950 person-years of follow-up, 1,121 deaths were documented, including 272 CVDs-related deaths and 156 cancer-related deaths. After adjusting for confounding factors, the daily eating frequency was linearly inversely associated with all-cause and CVDs-related mortality, and the HR (95% CIs) for per 1 time increment of eating frequency were 0.88 (0.80-0.98) and 0.77 (0.63-0.93), respectively. Sensitivity analyses showed that the main results and statistical significance were still stable. Conclusions: Higher eating frequency was independently related to lower all-cause and CVDs-related mortality in people with diabetes, which can be used as a potential strategy for the daily diet management among populations suffering from diabetes.